Exclusive breastfeeding among women with type 1 and type 2 diabetes mellitus - Leandro Cordero; Michael R. Stenger; Mark B. Landon; Craig A. Nankervis (BMC, 2022)
Abstract Objective To compare exclusive breastfeeding (BF) and BF initiation among 185 women with Type 1 and 212 women with Type 2 pregestational diabetes who intended exclusive or partial BF and delivered at ≥34 weeks of gestation. Methods Retrospective cohort study. At discharge, exclusive BF is direct BF or BF complemented with expressed breast milk. BF initiation is defined by exclusive or partial BF. Results Type 1 and Type 2 groups were similar in prior BF experience (69 vs 67%) but were different in intention to BF exclusively (92 vs 78%) and partially (8 vs 22%). Women in the Type 1 group were younger (median age 30 vs 33y), likely to be primiparous (47 vs 25%), have a lower median BMI (32 vs 36 kg/m2) and deliver by primary cesarean (37 vs 26%). Infants born to Type 1 women were more likely to be admitted to the NICU (44 vs 18%) and to have hypoglycemia (59 vs 41%). At discharge, exclusive BF among Type 1 was higher (34 vs 23%), partial BF was similar (47 vs 46%) while FF (formula feeding) was lower (19 vs 31%) than in the Type 2 group. BF initiation occurred in 81% of Type 1 and 69% of Type 2 women. Conclusion Intention to BF exclusively was higher in Type 1 women compared to Type 2. At discharge, exclusive BF and BF initiation were lower and FF higher in the Type 2 group highlighting the need for different strategies if lactation in this special population is to be improved.